Manajemen Keuangan Berkelanjutan di Pondok Pesantren: Pendekatan Kewirausahaan dan Tantangannya: Manajemen Keuangan Berkelanjutan di Pondok Pesantren: Pendekatan Kewirausahaan dan Tantangannya - Aripin, Jenal; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
Financial sustainability is a major challenge for Islamic boarding schools in ensuring the stability of education quality and daily operations. Many pesantren heavily rely on external donations and government aid, which are often unstable. Therefore, effective and innovative financial management strategies are necessary to achieve financial independence. This study aims to analyze the financial management of Bustanul Wildan Islamic Boarding School, focusing on funding source diversification and financial sustainability strategies. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with school administrators, direct observations, and financial document analysis. The findings reveal that the school successfully manages its funding through a combination of community donations, student fees, government assistance, and self-sustaining businesses such as cooperatives, agribusiness, and garment production. This strategy enhances the school’s financial stability and reduces dependency on external funding. The study’s implications highlight the importance of financial transparency, capacity-building in financial management, and strengthening entrepreneurship as a solution for financial sustainability. These findings provide valuable insights for other Islamic educational institutions in developing more independent and sustainable funding models..